Waste-based geopolymeric mortars with very high moisture buffering capacity. (10th December 2018) - De Rossi, A.; Carvalheiras, J.; Novais, R.M.; Ribeiro, M.J.; Labrincha, J.A.; Hotza, D.; Moreira, R.F.P.M.
Highlights: Construction wastes were used to produce high moisture buffering capacity. Addition of H2 O2 dramatically enhanced the mortars' moisture buffer value. Fly ash-based mortars presented low thermal conductivity. Abstract: In this study, lightweight waste-based geopolymeric mortars were evaluated for the first time regarding their potential to passively adjust indoor relative humidity (RH) levels. Geopolymer mortars were prepared using a mixture of fly ash (FA) and metakaolin (MK) as a binder, in a proportion of 75:25 wt% (FA:MK), construction and demolition waste as the fine aggregate and a pore forming agent in varying amounts. The results showed that the addition of a pore-forming agent to the compositions considerably increased the moisture buffer value (MBV) of the mortars, that is, from 0.80 (reference mortar) to 5.61 g/m 2 Δ%RH (mortar with highest porosity). The moisture buffering capacity shown by these eco-friendly mortars is higher than values reported for other binder materials and can be classified as excellent (MBV > 2 g/m 2 Δ%RH). The porous FA-based mortars also presented low thermal conductivity (as low as 0.19 W/m∙K), which suggests that these innovative binders could be simultaneously used for indoor moisture buffering and as low thermal conductivity materials.